Refractive Lens Exchange in Hyperopic Presbyopes with the Acrysof IQ Panoptix Intraocular Lens: One-Year Results and Analysis of the Literature - Nicula CA (Dove Medical Press, 2020)
Cristina Ariadna Nicula,1,2 Raluca Popescu,2 Anca Maria Rednik,3 Dorin Nicula,2 Adriana Elena Bulboaca,4 Ioana Stanescu5 1Department of Ophthalmology, Medicine and Pharmacy University “Iuliu Hațieganu”, Cluj Napoca, Romania; 2Oculens Clinic, Cluj-Napoca, Romania; 3Department of Ophthalmology, Eye County Hospital, Cluj-Napoca, Romania; 4Department of Pathophysiology, Medicine and Pharmacy University “Iuliu Hațieganu”, Cluj Napoca, Romania; 5Department of Neurology, Medicine and Pharmacy University “Iuliu Hațieganu”, Cluj Napoca, RomaniaCorrespondence: Cristina Ariadna NiculaDepartment of Ophthalmology, Medicine and Pharmacy University “Iuliu Hațieganu”, Cluj Napoca, RomaniaTel +40-722849575Email niculacristina65@yahoo.comPurpose: To assess the functional and refractive outcomes in hyperopia and presbyopia correction by clear lens exchange with the intraocular trifocal artificial lens (IOL) Acrysof IQ Panoptix implant at 1 year.Materials and Methods: A number of 128 eyes (64 patients) underwent clear lens exchange with placement of the trifocal IOL Acrysof IQ Panoptix implant for hyperopia and presbyopia. Prior to the surgery the patients had a complete ocular examination. In all cases the artificial lens was implanted in the bag without any intraoperative complications. Visual acuity (VA) at distance, intermediate and near and ocular refraction were evaluated at 4 weeks, 6 and 12 months postoperatively.Results: The mean age was 53.49 ± 7.377 years old (range 40– 73 years). As high as 51.57% of the patients were males and 48.43% were females. The mean achieved refraction was 0.26 ± 0.73D. Almost 60.93% of patients were within ± 0.25D of the target refraction, with 82.03% eyes within ± 0.50D of the planned correction. At 1 year after surgery, 96.45% of eyes had a stable refraction (p > 0.05). At 1 year, a total of 92.25%, 89.92% and 91.47% achieved a monocular uncorrected distance, intermediate and near visual acuity of 0.2 logarithm of the minimum angle of resolution or better, respectively. At the same time point, a total of 95.35%, 91.47% and 93.80% achieved a binocular uncorrected distance, intermediate and near visual acuity of 0.2 logarithm of the minimum angle of resolution or better, respectively. There was no statistically significant difference (p> 0.05) between the postoperative uncorrected and best corrected VA (distance, intermediate, near) at 6 months and postoperative uncorrected and best corrected VA (distance, intermediate, near) at 12 months. None of our patients had any intraoperative complications. Two cases (1.56%) developed posterior capsule opacification. Twelve patients (18.75%) complained about photic phenomena such as glare and haloes, but this symptom disappeared after 6 months postoperatively. As high as93.56% of patients had a high satisfaction with the outcomes of the surgery. Spectacle independence was obtained in 97.65% eyes.Conclusion: The Acrysof Panoptix trifocal artificial lens offers a good vision at distance, intermediate and near, with a good quality of vision and refraction.Keywords: trifocal artificial lens, hyperopia, presbyopia, clear lens exchange